PARTISIPASI MASYARAKAT DALAM UPAYA PENERAPAN MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH DI SEKOLAH DASAR ANDALAN KABUPATEN SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The aim of this research are (1) to know the existence of supporting organization in society participation in the elementary schools in sleman regency. (2) to know the participation, responsibility, and society support in the application of MPMBS (correlate in existence of school, society hope in education, decision making in excellent schools, management of quality improvement program, cooperation, and participation, (3) to know the supporting figuration/ society participation in education implementation in excellent schools, (4) to know the schools efforts to improving community participation in application of MPMBS in excellent schools.To get the accurate data, this research use qualitative method. Object of this research is the participation of the society in an effort to implementing MPMBS in Sleman regency, while the subjects of this study are principals, teachers and school committees are taken purposively. Collecting data in this study using in-depth interviews, observation, and documentation. The validity of the data to test the credibility of the data using means extending research and triangulation techniques by combining different data collection techniques. Analysis of the data using an interactive model analysis techniques developed by Miles and Huberman.The results of this research are society participation in the implementation effort in elementary schools MPMBS in Sleman regency, are: (1) on the fifth excellent elementary SD N 1 Godean , SD N 1 Sleman, SD N 1 Kalasan, SD N 1 Babarsari and SD N 2 percobaan were have organizations that support society participation of school committees and school committees have been carrying out the role and function properly; (2) there is involvement, responsibility and community support in the effort to be good MPMBS application (related with the existence of the school, linked to people's expectations will be held in the excellent elementary education, related to the decision-making process in excellent primary, associated with the management of the quality improvement program, associated with the process of cooperation and participation); (3) support/ society participation in the form of financial and non-financial; (4) There’s school efforts to improve community participation. It shows the readiness of the society to support the implementation of the MPMBS programs .